Efficacy of Endoscopic Over 3-branched Partial Stent-in-Stent Drainage Using Self-expandable Metallic Stents in Patients With Unresectable Hilar Biliary Carcinoma. Issue 6 (July 2015) - Uchida, Daisuke; Kato, Hironari; Muro, Shinichiro; Noma, Yasuhiro; Yamamoto, Naoki; Horiguchi, Shigeru; Harada, Ryo; Tsutsumi, Koichiro; Kawamoto, Hirofumi; Okada, Hiroyuki; Yamamoto, Kazuhide
Abstract : Background: The treatment of biliary stricture is crucially important for continuing stable chemotherapy for unresectable biliary carcinoma; however, there is no consensus regarding the use of hilar biliary drainage. In this study, we examined the efficacy of endoscopic over 3-branched biliary drainage using self-expandable metallic stents (SEMSs) in patients with unresectable malignant hilar biliary stricture (HBS). Methods: A total of 77 patients with unresectable HBS treated with a SEMS and chemotherapy were retrospectively reviewed. There were 59 patients with cholangiocarcinoma and 18 patients with gallbladder carcinoma. The patients were divided into 2 groups (4- or 3-branched group and 2- or 1-branched group) and compared with respect to the duration of stent patency and overall survival. Results: A comparison of the patients' baseline characteristics showed no significant differences between the 4- or 3-branched group and the 2- or 1-branched group. Neither the duration of patency nor survival time exhibited significant differences between the 2 groups, although, among the patients achieving disease control, the duration of patency period and survival time of the 4- or 3-branched group were significantly higher than those observed in the 2- or 1-branched group ( P =0.0231 and 0.0466). Conclusions: The use of endoscopic over 3-branched biliary drainage with a SEMS may improve the duration of patency in patients with HBS.